A prospective study of mifepristone and unlimited dosing of sublingual misoprostol for termination of second-trimester pregnancy in Uzbekistan and Ukraine. Issue 3 (4th June 2019) - Platais, Ingrida; Tsereteli, Tamar; Maystruk, Galyna; Kurbanbekova, Dilfuza; Winikoff, Beverly
Abstract : Introduction: We aimed to assess the feasibility and acceptability of a second-trimester medical abortion regimen using mifepristone and sublingual misoprostol with no maximum number of misoprostol doses in Uzbekistan and Ukraine. Methods: This prospective open-label study enrolled 306 women with pregnancies of 13–22 weeks in Uzbekistan (n=134) and Ukraine (n=172). Women took 200 mg mifepristone at a place of their choosing, and 24–48 hours later received 400 μg sublingual misoprostol every 3 hours until the expulsion of both fetus and placenta. Study staff interviewed women about the intensity of pain, side effects, and satisfaction with the procedure. The primary outcome was the rate of complete uterine evacuation without surgical intervention or oxytocin at 15 hours after the first dose of misoprostol. Results: The median gestational age was 18.1 weeks, and half of the women (n=149, 48.9%) chose to take mifepristone at home. The majority of women (n=266, 86.9%, 95% CI 82.6% to 90.5%) expelled by 15 hours after the start of misoprostol treatment, and by 48 hours complete uterine evacuation was achieved in 296 (96.7%) women. Most women found pain (76.1%) and side effects (89.0%) to be acceptable or very acceptable, and reported high satisfaction (89.8%) with the procedure. Conclusion: Medical abortion in pregnancies of 13–22 weeks with 200 mg mifepristone followed 24–48 hours later by 400 μg sublingual misoprostol administered every 3 hours until complete expulsion is effective, safe and acceptable to women. Women can be given the option to take mifepristone at home and return to the hospital. Clinical trials registration number: ClinicalTrials.gov, www.clinicaltrials.gov, NCT02415894, NCT02235155 .